Formation and Development of Corporate Social Responsibility Concept - A. Mostepaniuk (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article provides the conceptual study on the emerging and further development of the corporate social responsibility (CSR) starting from the late 1880es. The paper covers the most important transformations of the concept, starting from its understanding as a mechanism of redistribution of the wealth and continuing till the formation of the modern business strategy. The study investigates the main principles of CSR, the key arguments for and against the social performance of business, potential positive impact on society and challenges of CSR. The study concludes that key goals of CSR are modifying with other economic and social changes, shifts in public needs and requirements towards business, the possibility of public sector to provide and support basic human rights etc. The outcomes of the research are useful for business in order to implement correctly principles of CSR and avoid possible challenges, to impact positively social life and standards, as well as public sector while the process of institutionalization and forming the legal background of CSR.